Efficacy of Elbasvir/Grazoprevir Therapy in HCV Genotype-1 with or without HIV Infection: Role of HCV Core Antigen Monitoring and Improvement of Liver Stiffness and Steatosis. Issue 6 (August 2020) - Chayanupatkul, Maneerat; Chittmittraprap, Salyavit; Pratedrat, Pornpitra; Chuaypen, Natthaya; Avihingsanon, Anchalee; Tangkijvanich, Pisit
Background: The combination of elbasvir and grazoprevir (EBR/GZR) has been approved for treating HCV infection. This study aimed to evaluate the efficacy of EBR/GZR in terms of sustained virological response (SVR) and improvement of liver fibrosis in Thai patients with HCV genotype-1 (GT1). The utility of serum HCV core antigen (HCVcAg) as an alternative to HCV RNA in assessing SVR was also investigated. Methods: A total of 101 HCV GT1-infected patients (65 monoinfection and 36 HIV coinfection) who received EBR/GZR for 12–16 weeks were included. Liver stiffness (LS) and controlled attenuation parameter (CAP) were measured by transient elastography. Serum HCVcAg was measured in parallel with HCV RNA. Results: The overall SVR12 and SVR24 rates in the cohort were 98.0% and 95.0%, respectively. SVR24 rates were consistently high (90.0% to 100%) across all subgroups of patients. A significant LS decline ≥30% was observed more frequently in cirrhotic than non-cirrhotic individuals who achieved SVR (63.3% versus 30.3%; P =0.003). The magnitude of LS decline following HCV eradication was comparable between HCV monoinfection and HCV–HIV coinfection. The reduction of CAP was also observed in responders who had significant steatosis at baseline. Compared with HCV RNA, HCVcAg testing displayed high sensitivity (100%) and specificity (99.0–100%) in determining SVR12 and SVR24. Conclusions: This study confirms that EBR/GZR is effective for HCV GT1-infected Thai patients with or without HIV infection. HCV eradication is associated with LS and CAP improvement regardless of HIV status. HCVcAg testing could be a potential replacement for HCV RNA for assessing SVR in resource-limited settings.